The role of kairomones in prey finding by Diomus sp. and Exochomus sp. two coccinellid predators of the cassava mealybug, Phenacoccus manihoti - Meiracker, R.A.F. van der; Hammond, W.N.O.; Alphen, J.J.M. van (Wiley, 1990)
We studied searching behaviour of Diomus sp., a coccinellid predator introduced into Africa as a natural enemy of the cassava mealybug, when searching on cassava leaves, and compared its behaviour with the searching behaviour of Exochomus sp., an African predator of mealybugs (MB's). Female adults of Diomus and Exochomus spent more lime searching on cassava leaves previously infested with cassava MB than on clean cassava leaves, in response to substances produced by MB's (wax and/or honeydew) still present on these leaves as kairomones after removal of the MB's. Both species were also arrested by wax and/or honeydew of the citrus mealybug, Planococcus citri. When offered a choice between kairomones of both MB species only experienced Diomus (reared on cassava MB) showed a clear preference for kairomone of cassava MB. Separate influences of wax and honeydew were tested. Wax from cassava MB was an arrestment stimulus for both coccinellid species. Honeydew produced by cassava MB arrested Exochomus and inexperienced Diomus.